175k views
3 votes
Express your answer as a polynomial in standard form.f(x) = -3x + 1g(x) = 3x2 + 4x – 15Find: f(g(x))

Express your answer as a polynomial in standard form.f(x) = -3x + 1g(x) = 3x2 + 4x-example-1
User Bweber
by
5.2k points

1 Answer

1 vote

SOLUTION

Step1; Write out the expression


\begin{gathered} f(x)=-3x+1 \\ g(x)=3x^2+4x-15 \end{gathered}

Step2: Substitute the expression of g(x) for x into the F(x), we have


\begin{gathered} f(g(x))=-3(3x^2+4x-15)+1 \\ =-9x^2-12x+45+1 \\ \end{gathered}

Then


f(g(x))=-9x^2-12x+46

Therefore, F(g(x))=-9x²-12x+46

User Flyingturtles
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.